2012
DOI: 10.1007/s00167-012-2062-y
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon cause of cemented unicompartmental knee arthroplasty failure: fracture of metallic components

Abstract: Fracture of the metallic components is a potential cause of failure of unicompartmental knee arthroplasty. In our experience, the incidence of this complication was 4.9 % of all UKR failures. Patients with a BMI greater than 30 and a progressive deterioration in limb alignment were at greater risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…At five year follow-up, two cases were revised, one because of femoral component breakage and the other because of an unexplained painful tibial component, which was not improved, even after revision. Implant breakage in the early case was thought to have occurred as a result of using the original UKA design without the reinforced femoral fin [26,27]. Despite all the tibial failures seen at a long-term follow-up being in female patients there were no statististically significant genderbased differences in terms of failure.…”
Section: Discussionmentioning
confidence: 99%
“…At five year follow-up, two cases were revised, one because of femoral component breakage and the other because of an unexplained painful tibial component, which was not improved, even after revision. Implant breakage in the early case was thought to have occurred as a result of using the original UKA design without the reinforced femoral fin [26,27]. Despite all the tibial failures seen at a long-term follow-up being in female patients there were no statististically significant genderbased differences in terms of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors associated with unicompartmental component fracture included malalignment with increased local stresses due to malpositioning, progressive osteoarthritis, and cruciate ligament deficiency. Patients with a BMI greater than 30 were also at greater risk [27].…”
Section: Discussionmentioning
confidence: 98%
“…Han et al 9 and Furnes et al 10 suggested that significant osteolysis in the distal femur could lead to fatigue fracture because of the application of cyclic stresses on the femoral component. 9,10 In 2013, Manzotti et al 5 presented a series of unicompartmental knee replacement failures where high body mass index (median 32.4) is a common feature and diagnosis has been made in all cases with radiographs.…”
Section: Discussionmentioning
confidence: 99%